Bless me, Ultima [videorecording (DVD)] - Franklin, Carl, 1949-; Martinez, Benito, 1971-; Cosío, Joaquín; Heredia, Dolores; Ganalon, Luke; Colon, Miriam; Anaya, Rudolfo A. (Columbia, 2013)
In New Mexico in the time of WWII, a young man goes to an aged medicine woman and forms a relationship which helps him challenge the fight amid the good and the evil that storms through his village.